(untitled) (Eurasian Journal of Medical and Natural Sciences, 2026)
Stress is one of the major global health problems, increasing due to modern lifestyle factors such as rapid pace of life, social pressure, and информацион load. It negatively affects both psychological and physical health, especially in middle-aged individuals. Physiologically, stress is a nonspecific response of the body described by Hans Selye’s general adaptation syndrome, which includes alarm, resistance, and exhaustion stages. The main regulatory systems involved are the hypothalamic-pituitary-adrenal (HPA) axis and the sympathoadrenal system, which release stress hormones such as adrenaline, noradrenaline, and cortisol. Cortisol plays a key role in adaptation by regulating metabolism and maintaining homeostasis. While acute stress enhances adaptive capacity, chronic stress leads to dysfunction of regulatory systems, causing prolonged high cortisol levels, metabolic disturbances, and hormonal imbalance. Therefore, studying the relationship between stress and the endocrine system is an important area of modern medicine, particularly in understanding cortisol level changes under stress.